ILMU, ILMUWAN, DAN ETIKA ILMIAH - Buseri, Kamrani (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2014)
In the process of transferring knowledge from western country, it is inevitable that the pattern of the way of life and habits such as liberalism, hedonism, materialism, empirical and secular attitude was unconsiously adapted. Eventually, science can take man to be more distant from God as a source of spiritual values that is capable of delivering the ultimate goal of human life in the form of peace and harmony. In fact, science has now shifted so that it led to power fight as wellas mastery of the material competition which sometimes violates the social ethics and religion. A scientist is required to realize the negative values that come with science and make a positive factor combined with positive attitude as a beachhead for research in order to achieve the philosophical meaning of science to have a peaceful and prosperous community.